PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL,PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN UTANG - Ade Imam Muslim; Irna Fitria Puspa (Program Studi Akuntansi, Universitas Kuningan, 2019)
This research aiming to know influence managerial ownership, institutional ownership, sales growth and size to debt policy. Independent variable in this research is managerial ownership, institutional ownership, sales growth and size, while dependent variable in this research is debt policy. This research using descriptive and verification method. Population in this research is company sub sector automotive and component has registered in Bursa Efek Indonesia period 2013 until 2017. Sample in this research determined using purposive sampling technique. From 13 company, has been obtained 8 company has fulfilling criteria for became research sample. The research result showing a partial managerial ownership has positive effect to debt policy, institutional ownership has no take effect to debt policy, sales growth has negative effect to debt policy and size has no take effect to debt policy. Other than that , in a manner simultaneous managerial ownership, institutional ownership, sales growth and size have taken effect to debt policy by 95,13%.Keyword : Debt Policy, Managerial Ownership, Institutional Ownership, Sales Growth.